Evolution of the rhytidectomy - Dane M. Barrett (KeAi Communications Co., Ltd., 2016)
Since the advent of facelift surgery, there has been a progressive evolution in technique. Methods of dissection trended towards progressively aggressive surgery with deeper dissection for repositioning of ptotic facial tissues. In recent decades, the pendulum has swung towards more minimally invasive options. Likewise, there has been a shift in focus from repositioning alone to the addition of volumization for facial rejuvenation. The techniques in this article are reviewed in a chronologic fashion with a focus on historical development as well as brief discussion on efficacy in relation to the other existing options. There is currently no gold standard technique with a plethora of options with comparable efficacy. There is controversy over which approach is optimal and future research is needed to better delineate optimal treatment options, which may vary based on the patient. Keywords: Rhytidectomy, Facelift, Facelift techniques, History of the facelift, Facial rejuvenation, Facial fillers, Autologous fat transfer